Inflation forecasts' performance in Latin America - Jo\~ao Tovar Jalles (Review of Development Finance, 2017)
This paper provides a full characterization of inflation rate forecasts using the mean values from Consensus Economics for a sample of 14 Latin American countries between 1989 and 2014. It also assesses the performance of inflation rate forecasts around business cycles' turning points. Results show that inflation forecasts in the region display the standard property that as the forecast horizon shortens accuracy improves. On average, forecasters underpredict inflation, but this masks very different country experiences. We find evidence point to biasedness of inflation forecasts for year-ahead forecasts but not for current year. Tests' results point to forecast inefficiency which is also evidenced by a tendency to smooth them between revisions. Focusing on business cycle turning points, forecasters tend to slightly underpredict the inflation rate and the extent of underprediction increases during recessions. The hypothesis of forecast efficiency is overwhelmingly rejected both during recessions and recoveries.
Keywords: C53; E27; E37; E62; D8; 650; Forecast comparison; Bias; Efficiency; Information rigidity; Recession; Recovery